Novel bodies : disability and sexuality in eighteenth-century British literature - Farr, Jason S., 1978- (Transits (Bucknell University), 2019)
Novel Bodies examines how disability shapes the British literary history of sexuality. Jason Farr shows that various eighteenth-century novelists represent disability and sexuality in flexible ways to reconfigure the political and social landscapes of eighteenth-century Britain. In imagining the lived experience of disability as analogous to--and as informed by--queer genders and sexualities, the authors featured in Novel Bodies expose emerging ideas of able-bodiedness and heterosexuality as interconnected systems that sustain dominant models of courtship, reproduction, and degeneracy. Further, Farr argues that they use intersections of disability and queerness to stage an array of contemporaneous debates covering topics as wide-ranging as education, feminism, domesticity, medicine, and plantation life. In his close attention to the fiction of Eliza Haywood, Samuel Richardson, Sarah Scott, Maria Edgeworth, and Frances Burney, Farr demonstrates that disabled and queer characters inhabit strict social orders in unconventional ways, and thus opened up new avenues of expression for readers from the eighteenth century forward. Published by Bucknell University Press. Distributed worldwide by Rutgers University Press.